SHARING SESSION MANAJEMEN KEUANGAN BISNIS DAN PENGELOLAAN PANGAN YANG BAIK DI MASA PANDEMI - Laras Cempaka; Nurul Asiah (LPPM Universitas Abdurrab, 2022)
are usually carried out directly are now slightly different, namely by using an online platform. However, this does not reduce the essence of devotion itself. It is hoped that the expertise possessed by permanent lecturers can be channeled and beneficial to the people around them. In this service, the theme is Sharing Session on Business Finance and Good Food Governance in a Pandemic Period. The goal is to educate the public, especially the PDM Market buying and selling community, so that they can have a better muamalah. The material provided consists of managing business finances and good food processing during a pandemic. As a result, members of this community can determine the selling price of food products appropriately, optimize the profits that will be generated, process food with good sanitation and hygiene and can apply it to realize food safety for consumers.